Development of PBL-Integrated Augmented Reality Media to Improve Mutual Cooperation and National Ideology Education Learning Outcome for Fifth-Grade Students - Alfinnaja, Navira; Aeni, Kurotul (Jurnal Pendidikan Progresif, 2025)
Development of PBL-Integrated Augmented Reality Media to Improve Mutual Cooperation and National Ideology Education Learning Outcome for Fifth-Grade Students. Purpose: The purpose of this study was to develop Augmented Reality media with a Problem Based Learning model to improve the dimensions of mutual cooperation and learning outcomes of fifth grade students at SDN Pandansari 01, Batang Regency, in national ideology education, specifically the material on mutual cooperation in the surrounding environment. Methods: This study used a Research and Development (R&D) approach using the Borg & Gall model for development, which consists of eight stages, namely 1) Potential and problems; 2) Data collection; 3) Product desain validation; 4)Product design validation; 5) Design revision; 6) Product testing; 7) Product revision; 8) Usage testing. Findings: The learning device developed in the form of AR-based flashcards containing examples of mutual cooperation application in the surrounding environment. Evaluation by subject matter experts yielded a a score of 85.4 while media experts scored. 90.2 indicating that the material and media validation results fall into the highly suitable category. Testing was conducted on 31 fifth grade elementary school students, showing a significant increase in the mutual cooperation dimension and students learning outcomes. Statistical analysis based on the t-test showed a result of 0,001, indicating significant effect on the pretest and posttest result. The n-Gain test was 0,71, indicating a high category. Conclusion: The conclusion of this study is that AR-based learning media with PBL model is effective in improve learning outcomes and the application of mutual cooperation in national ideology education. Keywords: augmented reality, mutual cooperation dimension, learning outcomes, national ideology education.